ANALISIS PENERAPAN HARGA POKOK PRODUKSI PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) PABRIK ROTI TAENG DI GOWA - Daryanti Daryanti; Neng Indriyani (AkMen JURNAL ILMIAH, 2020)
This research was conducted with the aim of knowing the application of the cost of production carried out by the Micro, Small and Medium Enterprise (UMKM) Pabrik Roti Taeng di Gowa. This is important considering that the calculation of the exact and detailed cost of products is needed as a basis in determining the right selling price to increase the company's income (profit). Pabrik Roti Taeng is one of the business activities that in applying the cost of production still uses a simple method. In this study, the calculation of cost of production uses the full posting method. Data analysis used is descrptive and comparative method. Production costs are calculated based on estimates. In addition, the company does not take into account fixed factory overhead costs such as depreciation of machinery and equipment into production costs